Examining the impact of age on chemotherapy completion in epithelial ovarian, fallopian tube and primary peritoneal cancer: a retrospective cohort study in Thailand - Natacha Phoolcharoen; Ruangsak Lertkhachonsuk; Sasivimon Ratree; Somsook Santibenchakul; Nicha Assavapokee (BMJ Open)
Objective To explore the difference in chemotherapy completion and reasons for discontinuation between older (≥70 years) and younger (<70 years) patients.Design Retrospective cohort study.Setting Single tertiary centre in Thailand.Participants The patients who received chemotherapy from 1 January 2009 to 30 June 2021 were included and followed up until 30 June 2022. Of the 757 patients with epithelial ovarian, fallopian tube and primary peritoneal cancer (EOC), 108 were in the older group and 649 were in the younger group.Primary and secondary outcome measures The difference in chemotherapy completion, the association between younger and older patients and early discontinuation of chemotherapy.Results The proportion of chemotherapy completion was significantly lower in older versus younger patients (84.3% versus 92.6%, p=0.007). Excluding discontinuation due to disease progression, the chemotherapy completion was comparable (93.5 versus 95.7%, p=0.456). Dose reduction and grade 3–4 hematotoxicity occurred more often in the older group. The univariable logistic regression model showed that older age (≥70 years) was significantly associated with early chemotherapy discontinuation (OR 2.39; 95% CI 1.29–4.24). However, after adjusting for potential confounders, age was not significantly associated with early discontinuation (OR 1.20; 95% CI 0.54–2.66). Multiple comorbidities and types of surgery were identified as independent risk factors for chemotherapy discontinuation.Conclusion The completion of chemotherapy was observed in a majority of older adults with EOC. Age is not the only determinant of chemotherapy completion. Comorbidity and disease status are crucial for determining chemotherapy discontinuation.